Analisis Beban Kerja dengan Metode Work Sampling Pada Pegawai Bidang Akademik (Studi Kasus: Fakultas Teknik di Perguruan Tinggi X) - Hery Murnawan; Febrian Puji Lestari (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Workload is a measure of each individual's performance of their duties and authority according to the SOP, within the specified working hours, and the results must meet the target. Workload can refer to the level of productivity and performance of employees in an organisation. The Faculty Unit at College X is one of the work units under the auspices of the Rector of the College. This research uses the observation method as a data collection technique and the work sampling method as a data analysis method. The results of the research show that the educational staff with the position of administrative implementer of the 1st civil engineering study programme have the highest workload with 86.6%, and the lowest workload belongs to the administrative implementer of the 1st civil engineering study programme with 58.1%. The average standard time needed to complete an activity is 22.9 minutes, so it is recommended to have an even distribution of workload.